THE STUDY OF THE KINETICS OF THE MIXING PROCESS THE RAW FISH AND PLANT COMPONENTS - Albert Hamed-Harisovich Nugmanov; Igor Yuryevich Aleksanyan; Artem Igorevich Aleksanyan (Современная наука и инновации, 2022)
The article is devoted to the study of kinetics and analysis of the regularity of the process of mixing offish raw materials and vegetable component to obtain a minced mixture in the technology of frozen semi-finished products, since the introduction of vegetable premix in fish minced meat will reduce the amount of free moisture in the product and thereby reduce the time for freezing.